Experimental treatment of multiple myeloma in the era of precision medicine. Issue 1 (2nd January 2016) - Di Martino, Maria Teresa; Arbitrio, Mariamena; Guzzi, Pietro Hiram; Cannataro, Mario; Tagliaferri, Pierosandro; Tassone, Pierfrancesco
ABSTRACT: Precision medicine is the selection of appropriate treatments to individual patients on the basis of molecular predictive factors and clinical presentation. In this light, multiple myeloma (MM) represents a challenging area of investigation for its biological complexity and close interplay with cell components of the bone marrow microenvironment. Here, we discuss personalized strategies for MM treatment with specific focus to the integrated molecular profiling, the emerging role of non-coding RNA therapeutics and novel pharmacogenomics tools. Precision medicine of MM is still in its infancy but the rapidly increasing knowledge and technological advancements will offer major opportunities for crucial changes of the treatment paradigm in the next future.